2000
DOI: 10.1038/sj.ijo.0801506
|View full text |Cite
|
Sign up to set email alerts
|

The role of lipoprotein lipase in adipose tissue development and metabolism

Abstract: Lipoprotein lipase (LPL) is essential for the hydrolysis and distribution of triglyceride-rich lipoprotein-associated fatty acids among extrahepatic tissues. Additionally, the enzyme facilitates several non-lipolysis associated functions including the cellular uptake of whole lipoprotein particles and lipophilic vitamins. The tissue-speci®c variations of LPL expression have been implicated in the pathogenesis of various lipid disorders, obesity and atherosclerosis. Transgenic technology provided the means to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0
4

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 20 publications
(15 reference statements)
1
44
0
4
Order By: Relevance
“…Our findings complement the data of Yagyu et al (12), who showed decreased VLDL-TG catabolism in vldlr Ϫ/Ϫ mice that had fasted for 16 h. However, they observed no change in the uptake of VLDL-TG by adipose tissue and a reduced uptake by heart and muscle in VLDLr deficiency, whereas we find a significantly decreased uptake of chylomicron-like emulsion TG by adipose tissue with no consistent reduction in uptake of TG by heart or muscle. Although substrate variation (i.e., emulsion particles vs. native VLDL) may have contributed to the observed discrepancy, the differences between the two studies can be fully explained by the natural regulation of tissue LPL levels by the feeding state, as prolonged fasting induces a gradually decreased expression of LPL by adipose tissue whereas that of heart and muscle is gradually increased (13,(19)(20)(21)(22)(23). Furthermore, under fed conditions, the flux of TG-derived FFAs to adipose tissue is greatly enhanced compared with the fasting state (14).…”
Section: Discussionmentioning
confidence: 94%
“…Our findings complement the data of Yagyu et al (12), who showed decreased VLDL-TG catabolism in vldlr Ϫ/Ϫ mice that had fasted for 16 h. However, they observed no change in the uptake of VLDL-TG by adipose tissue and a reduced uptake by heart and muscle in VLDLr deficiency, whereas we find a significantly decreased uptake of chylomicron-like emulsion TG by adipose tissue with no consistent reduction in uptake of TG by heart or muscle. Although substrate variation (i.e., emulsion particles vs. native VLDL) may have contributed to the observed discrepancy, the differences between the two studies can be fully explained by the natural regulation of tissue LPL levels by the feeding state, as prolonged fasting induces a gradually decreased expression of LPL by adipose tissue whereas that of heart and muscle is gradually increased (13,(19)(20)(21)(22)(23). Furthermore, under fed conditions, the flux of TG-derived FFAs to adipose tissue is greatly enhanced compared with the fasting state (14).…”
Section: Discussionmentioning
confidence: 94%
“…Some of the sexually dimorphic effects of p47 phox absence on adipocyte hypertrophy appeared to be associated with reduced uptake of fatty acids. Both LPL, which is involved in hydrolysis of serum triglycerides to fatty acids for adipocyte uptake (45), and CD36, which transports free fatty acids into adipocytes (35), were suppressed at the mRNA and protein level. Both enzymes are downstream targets of the transcription factor PPAR␥ (35,46).…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein lipase (LPL) is one of the important factors for lipid deposition in adipose tissue (Zechner et al, 2000). An in vitro study with 3T3-L1 pre-adipocytes showed that during differentiation, LPL mRNA expression increased sixfold; this resulted in a twofold increase in cell surface-associated LPL and a 10-fold increase in intracellular lipid storage (Gonzales and Orlando, 2007).…”
Section: Introductionmentioning
confidence: 99%